Caliche and Seawater, Sources of Nitrate and Chloride Ions to Chalcopyrite Leaching in Acid Media - Pía Hernández; Giovanni Gahona; Monserrat Martínez; Norman Toro; Jonathan Castillo (Metals, 2020)
Hydrometallurgical processing of chalcopyrite is of great interest today due to the depletion of oxidized copper minerals. This will also enable existing plants to continue operation. The objective of this work is to study the behavior of chalcopyrite leaching by stirring in an acid-nitrate-chloride media where seawater and brines provide chloride ions and nitrate ions can be provided from the caliche industry. The variables studied were sulfuric acid, nitrate and chloride concentration, source of water (dissolvent), temperature, solid/liquid ratio, particle size, mineral sample, and pretreatment before the leaching process. Despite being a refractory mineral, chalcopyrite can be leached in this system obtaining favorable recoveries at the conditions studied. It was possible to obtain 50% Cu in 0.7 M of H2SO4 and NaNO3, using brine at 45 °C. The nitrate-chloride-acid system was highly temperature dependent, with an activation energy of 82.6 kJ/mol, indicative of chemical reaction control of leaching kinetics. SEM/EDS indicated the presence of sulfur on the surface of the mineral after leaching. This study demonstrates that sources such as seawater or discard brines (such as from the reverse osmosis process) and waste (solid or solutions) from the caliche industry can provide a highly oxidative system for the dissolution of chalcopyrite.